1983
DOI: 10.1159/000117964
|View full text |Cite
|
Sign up to set email alerts
|

Effects of DSIP in Man

Abstract: Animal experiments confirmed the neuropeptide nature of delta-sleep-inducing-peptide (DSIP) and a species-specific sleep promotion. Five different human studies were carried out with single and repeated intravenous injections of DSIP under double-blind conditions, and with assessing treatment effects by psychophysiological tests and polygraphic recordings. Compatibility of DSIP was good. Slow injection proved essential. A latency of sleep induction of 1 h, but a duration of up to 20 h was found. The somnogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 19 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…The results of the present study indicated that 3 doses of DSIP showed at best some weak effects. Schneider-Helmert and Schoenenberger [9] reported to adminis ter DSIP in the morning, whereas in our study it was given at the end of the afternoon. It seems however unlikely that the different time of the administration could explain the Note: The subjective sleep quality scale ranges from 0 (low sleep quality) to 14 (high sleep quality).…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…The results of the present study indicated that 3 doses of DSIP showed at best some weak effects. Schneider-Helmert and Schoenenberger [9] reported to adminis ter DSIP in the morning, whereas in our study it was given at the end of the afternoon. It seems however unlikely that the different time of the administration could explain the Note: The subjective sleep quality scale ranges from 0 (low sleep quality) to 14 (high sleep quality).…”
Section: Discussionmentioning
confidence: 54%
“…Important improvements in the amount and stability of sleep in insomniac patients have been reported after the administration of 3 doses of DSIP [9], This, in addi tion to practical limitations prompted us to adopt a design with the administration of no more than 3 doses of DSIP. The results of the present study indicated that 3 doses of DSIP showed at best some weak effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some patients reported that their sleep stayed improved for individually varying, prolonged periods following DS1P adminis tration [12]. Since impaired daytime func tions are clinically among the most impor tant symptoms of insomnia, it is noteworthy that daytime alertness, performance and even memory functions were found to be higher at daytime following DSIP adminis tration in the morning, suggesting that DSIP might act directly on the regulation of awake behaviour in addition to sleep [10,13,14]. The present study aimed at further elaborat ing these findings within a 24-hour psychophysiological investigation of sleep and day time functions in severe chronic insom niacs.…”
mentioning
confidence: 99%